Posting to impress? Organizational impression management tactics multinational firms employ to showcase innovations supporting SDGs - Frutos-Bencze, Dinorah; Bachmann, Pavel; Gigliotti, Robert; Ježek, Bruno (Journal of cleaner production, 2024)
Multinational enterprises (MNEs) play a significant role in promoting innovation and implementing Sustainable Development Goals (SDGs). MNEs have embraced social media use not only to promote themselves, but also to engage with various stakeholders. Using mixed methods such as Python programming scripts, big data analysis, text analysis and coding, this study explores Facebook (FB) communications specific to innovation and SDGs (ISDG). The study's findings suggest that only approximately 2.7% of the overall communications are about ISDGs. The frequency of ISDG communications varies by industry category and region, but public engagement only varies by industry. Additionally, the study found that MNEs predominantly use assertive organizational impression management (OIM) tactics in their ISDG communications. Our analysis also suggests that ISDG communications tend to focus on SDGs that impact positive externalities rather than negative ones. Overall, our findings indicate that slowly but surely most MNES are laying down the foundation for possibly adopting innovations related to the implementation of SDGs.